Membaca lukisan Agus Suwage:`The Super Omnivore` - Indrawati, Lilik (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Appreciating Indonesian contemporary paintings created by Agus Suwage must be related to the painter’s background, existence, culture, and the condition of the national environment. Suwage mostly exploits himself as an object that later becomes a medium to express his restlessness through ideas. The self-portrait objects in Suwage’s paintings function as metaphoric icons. However, the portraiture techniques chosen by Suwage in his works do not narrate a personal story about himself.